PENGETAHUAN PENDUDUK DESA KARANGWANGI CIANJUR JAWA BARAT TENTANG JENIS, TEKNIK PENANGKAPAN, DAN GANGGUAN TERHADAP IKAN SUNGAI CIKAWUNG - Tatang Suharmana Erawan; Johan Iskandar; Toni Nuari (Jurnal Pro-Life, 2017)
Villagers Karangwangi, South Cianjur, West Java hereditary has leveraged diversity of fish in the river Cikawung. As a result, residents have traditional ecological knowledge about the types of fish in the river Cikawung. The purpose of this study is assessing the knowledge of the villagers Karangwangi, about the types of fish and a variety of fishing techniques, as well as a variety of disorders of the types of fish in the river Cikawung. The method used a qualitative approach and ethnobiology etnozoologi, with data analysis by descriptive analysis. The results showed that it had recorded 33 species of fish but only six types of fish population is quite a lot. Nine technique known population in catching the types of fish in the river but now there has been a change in fishing are not environmentally friendly and cause disturbance to fish populations. The study concludes that in order to be able to harvest a variety of river fish sustainably Cikawung and sustain the lives of a variety of river fish Cikawung, need to change people's behavior in using the types of fish and the promotion of various safeguards. Keywords: Karangwangi, traditional ecological knowledge, fish species, fishing techniques, River Cikawung